Peran Orang Tua Terhadap Pendidikan Karakter Anak - Bayu Bayu Widiyanto; Nurfaizah Nurfaizah (Jurnal DinamikA, 2023)
This study aims to determine and describe the role of parents on children's character. This type of research is a literature review obtained from journals on the internet. The data collection technique is to listen and record the things needed in this study. Data validity techniques use triangulation techniques, namely data reduction, data display, and drawing conclusions. The results of this study are that parents play an important role in children's character education, especially in 5 aspects, namely (1) parents as educators, (2) parents as facilitators, (3) parents as companions and supervisors, (4) parents as motivators, and (5) parents as figures / role models for children.